2013
DOI: 10.1093/cid/cit489
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Children and Adolescents With Juvenile Idiopathic Arthritis and Inflammatory Bowel Disease Treated With Tumor Necrosis Factor-  Inhibitors: Systematic Review of the Literature

Abstract: Tumor necrosis factor alpha (TNF-α) inhibitors are increasingly administered to children and adolescents with juvenile idiopathic arthritis (JIA) and pediatric inflammatory bowel disease (pIBD). Adult studies indicate that TNF-α inhibitors lead to an increased risk of serious infections compared to other disease-modifying antirheumatic drugs. We report herein a systematic literature review detailing the epidemiology and types of infections reported in children with JIA and pIBD treated with TNF-α inhibitors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 110 publications
3
60
0
4
Order By: Relevance
“…Early recognition is important because the clinical outcome depends upon the stage at which therapy is initiated 1 . A recently published review article reported 5 cases of TB occurring in pediatric patients while they were taking anti-TNF treatment 6 . Herein, we report the first fatal case of TBM in a child taking anti-TNF therapy; the child's cerebrospinal fluid (CSF) sample tested negative for Mycobacterium tuberculosis on polymerasechain reaction (PCR), was smear negative for acid-fast bacilli (AFB), and had a low level of adenosine deaminase (ADA).…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition is important because the clinical outcome depends upon the stage at which therapy is initiated 1 . A recently published review article reported 5 cases of TB occurring in pediatric patients while they were taking anti-TNF treatment 6 . Herein, we report the first fatal case of TBM in a child taking anti-TNF therapy; the child's cerebrospinal fluid (CSF) sample tested negative for Mycobacterium tuberculosis on polymerasechain reaction (PCR), was smear negative for acid-fast bacilli (AFB), and had a low level of adenosine deaminase (ADA).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 A recent large-scale review of pediatric patients on TNF-a inhibitors for JIA or inflammatory bowel disease found that the occurrence of severe fungal infections was rare and often confounded by the presence of concurrent immunosuppressive therapy in affected patients. 7 Only 4 of 4625 pediatric patients with JIA on TNF-a inhibitors were noted to develop infection with histoplasmosis, and no blastomycosis infections were reported. Although previously reported in adults, ours is the first case in the literature, to our knowledge, of a pediatric patient developing infection with B dermatitidis after initiation of infliximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although tumor necrosis factor-a (TNF-a) inhibitors carry a US Food and Drug Administration warning of increased risk for fungal infections, the evidence of such risk is thus far limited in pediatric patients. 6,7 We present the case of a 9-year-old boy on therapy with infliximab and methotrexate for juvenile idiopathic arthritis (JIA) who presented with a nonhealing, indurated plaque of his right earlobe without systemic findings. He was ultimately diagnosed with cutaneous B dermatitidis.…”
mentioning
confidence: 99%
“…Cytokine inhibitors are thought to improve the patients clinical course by impairing the ability of TNF-α or IL-1 to bind to their receptors, inactivating the sepsis cascade cytokines, inhibiting production of inflammatory cytokines, and preventing further inflammation and damage to tissue or joints. However, this inhibition can potentially extend the susceptibility of patients to infections due to this downregulation of the immune system [40] [41].…”
Section: Discussionmentioning
confidence: 99%